The role of crises in shaping financial systems : from the Global Financial Crisis to COVID-19 /: from the Global Financial Crisis to COVID-19. (2022) - Iwanicz-Drozdowska, Małgorzata; Malinowska-Misiąg, Elżbieta; Mielus, Piotr, 1973-; Smaga, Pawel; Witkowski, Bartosz
No abstract available